Gender and the Conceptualization of Religion and Islam - Maltese, Giovanni (Implicit Religion, 2023)
The critique of power asymmetries reproduced by Eurocentric and essentialist conceptualizations of generic terms and analytical concepts is well-established in religious studies and gender studies, especially when investigating Islam. Yet each discipline is in danger of omitting the most critical discussions of the other. Discussions about conceptualizations of religion and Islam, even those adapting theoretically sophisticated global history approaches, largely ignore gender. Scholars of gender studies, in turn, have barely queried or nuanced “religion” and “Islam” as categories. Thus, they fail to take into account how conceptualizations of religion and Islam as generic terms have affected the power relations under scrutiny. This article aims to address this momentous mutual exclusion by examining a tract published in 1940 in the context of Anglophone Southeast and South Asian Muslim intellectual circles. Drawing on Judith Butler’s critical engagement with Luce Irigaray and on Butler’s notion of subversion by thoroughgoing appropriation and redeployment and situating this case study within the mentioned mutual exclusion, I argue that studying the relation between concepts of femininity and masculinity and concepts of religion and Islam poses important questions regarding colonial, androcentric, and phallogocentric epistemologies underlying contemporary religious studies and gender studies. I contend that religion-making and gender-making should not be investigated apart from each other.
CRIS-Team Scopus Importer:2024-03-27
Keywords: 1930s/40s South and Southeast Asia; feminism; gender studies; Global Religious History; Islam and gender; masculinity/femininity